INTEGRATED VISUAL SYSTEM DESIGN FOR ACADEMIC LIBRARIES: AN ACTION STUDY TO IMPROVE BRAND IDENTITY, AUDIENCE UNDERSTANDING, AND TEAM EFFICIENCY - Razif Abdussalam; Agus Rusmana; Kusnandar Kusnandar (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
Academic libraries often face the challenge of visual inconsistency on social media due to the lack of a standardized design system, which can weaken brand identity and communication effectiveness. This study aims to design, implement, and evaluate an integrated visual system to address this issue. The method used was Action Research, conducted in two cycles, adopting the Kemmis and McTaggart model. Data collection was carried out comprehensively through interviews with managers, observations, and questionnaires distributed to the audience (n=12). The study resulted in an integrated visual system consisting of a visual guideline (SOP) and a series of design templates in Canva, which was proven to significantly improve the team's workflow efficiency. Audience validation showed a very positive response, with all respondents (100%) stating that the new design was easy to understand, aligned with the brand identity, and visually consistent across all tested indicators. In conclusion, this study contributes by producing a practical and proven sustainable integrated visual system model. This model explicitly offers operational solutions for non-designer teams in library environments, an applicable approach that distinguishes it from previous research.